정치와 행정의 분열에 관한 계보학적 고찰: Giorgio Agamben의 「왕국과 영광」을 중심으로 - 이문수; Lee¸ Moon-soo (한국거버넌스학회보, 2020)
정치를 주권을 형성하고 이를 입법화시키는 것으로 보고, 행정은 입법화된 주권적 의지를 실행하는 것으로 볼 때, 언제부터 어떤 이유로 정치와 행정이 분리된 것으로 사유되기 시작했는지는 쉽게 접근하기 어려운 문제이다. 본 논문은 이태리 출신 철학자인 Giorgio Agamben의 최근의 저작들을 중심으로 2000년 동안의 서양의 통치기계는 본질/주권/정치라는 축과 실천/오이코노미아/행정이라는 축을 중심으로 하는 양극체제를 형성하면서 발전해왔음을 논증하는 것을 목적으로 하고 있다. Agamben은 서양 존재론에 깃들어있는 “존재와 실천, 초월적 선과 내재적 선, 신학과 오이코노미아” 사이의 근본적 분열의 기원을 표식이라는 방법론을 사용하여 추적한다. 그리고 이러한 분열은 동시에 ‘왕은 군림하지 통치하지 않는다’라는 전승을 현실화 시키는 왕국과 통치의 양극적 기계를 형성하는 계기가 된다. 그러나 Agamben의 주된 관심은 의심의 여지없이 위의 분열에서 후자, 즉 통치의 내재적, 행정적 측면에 놓여 있다. 그리고 왕국과 통치의 양극적 기계의 성립에 대한 그의 주장은 삼위일체 교의, 섭리와 운명에 대한 신학적 해석을 거처 Rousseau가 ｢사회계약론｣에서 말하는 일반의지와 개별의지의 구별을 통해 현대에 까지 유효한 것이 되고 있다. This article takes a close look at the Giorgio Agamben’s argument that the governmental machine of the Western world for two millennia has consisted of two poles of sovereignty and government, as an attempt to track down the beginning of the public administration. With its aim of refuting the traditional assertion regarding the dichotomy of politics and public administration, this study considers Agamben’s economic theology as providing us with a fresh perspective that can both broaden and deepen the research on the origin of public administration. Specifically, power operates as a bipolar machine, it articulates the transcendent pole of sovereignty and the immanent pole of administration, kingdom and government, auctoritas and potestas, political theology and economic theology. This is the structure of what Agamben calls the governmental machine. In this article, I reconstruct Agamben’s archaeology of economic theology as developed in The Kingdom and the Glory, tracing the signature of secularization to explain the overwhelming domination of the public administration and the operations of the governmental machine. I focus on the paradigm of oikonomia and its implications for the understanding of the articulation between sovereignty and governmentality. I conclude the article by indicating that Agamben’s account of the bipolar machine of power can easily face the dilemma coming out of his methodology of presuppositional argument. In other word, for Agamben there is no way out of the myth, “the king reigns, but does not govern,”